A Cognitive Linguistic Study of Visual Language as a Reflection of Culture: Violence Against Women in Iraq (Journal of the College of Education for Women, 2023)
The present work is qualitative descriptive. It aims to examine the idiosyncratic schema when deciphering the selected violence-based panel from Nasser Ibrahim’s caricatures. The researchers accordingly adopted part of Sharifian’s (2011) Cultural Schema model, particularly that part that is concerned with the examining the micro/idiosyncratic level of understanding. The study has revealed that the participants have not only differed among themselves regarding the way a figure is being denotatively conceptualized, they also highlighted different exact conceptualizations for the same figure, such as: using various adjectives that reflect various levels of intensity, emphasizing the behavioral aspect or the appearance of the figure, adopting different patterns of thinking like: metaphoric, metronomic, generic, specific, comprehensive or linear. Besides, based on their various points of attention and cognitive schema, they varied in conceptualizing the type of violence being depicted in this image as: psychological, verbal, physical, domestic violence or as the combination of more than one type. Finally, knowing about cultural schema does not involve to exemplify them in one’s behavior.